Association between shift work and biological factors including FGF-23, klotho, and serum 25-(OH) vitamin D3 among Korean firefighters: a cross-sectional study. Issue 10 (29th April 2020) - Min, Jeehee; Jang, Tae-Won; Ahn, Yeon Soon; Sim, Chang Sun; Jeong, Kyoung Sook
Abstract: Study Objectives: Shift work is known to be detrimental to an individual's health as it disrupts the circadian rhythm and is a risk factor for cancer. It has been reported that elevated fibroblast growth factor (FGF)-23, increased serum soluble α-klotho, and decreased vitamin D3 are associated with cancer progression. We studied the relationship between shift work and the levels of FGF-23, α-klotho, and vitamin D3 amongst firefighters, as they work in long shifts outside the traditional daytime schedule. Methods: The study consisted of 450 participants who were firefighters. We measured FGF-23, α-klotho, and vitamin D3 levels in their blood and a set of questionnaires were given to the participants to evaluate their health habits. After determining and adjusting for potential confounding factors, we compared the levels of FGF-23, α-klotho, and serum vitamin D3 by job and shift types. Results: FGF-23 and α-klotho levels were significantly higher in shift workers than traditional day workers, and in 3-day cycle shift workers than workers with another shift schedule. When the levels of these substances were compared based on different types of jobs, firefighters had a lower level of vitamin D3 . We conclude that shift work is positively correlated with the levels of FGF-23 and α-klotho. Conclusions: Levels of FGF-23 and α-klotho were linked to shift work and job types. Although vitamin levels did not differ by shift types, vitamin D3 levels were lower in firefighters. These findings suggest that high levels of FGF-23 and α-klotho are potential risk factors for cancer among firefighters.